Wasteful Azo Dyes as a Source of Biologically Active Building Blocks - Fernandes, Ana; Pinto, Bruna; Bonardo, Lorenzo; Royo, Beatriz; Robalo, M. Paula; Martins, Lígia O. (Frontiers in Bioengineering and Biotechnology, 2021)
In this work an environmental-friendly enzymatic strategy was developed for the valorisation of dye-containing wastewaters. We set-up biocatalytic processes for the conversion of azo dyes representative of the main classes used in the textile industry into valuable aromatic compounds: aromatic amines, phenoxazinones, phenazines and naphthoquinones. Firstly, using purified preparations of enzymes, we show that PpAzoR azoreductase efficiently reduce mordant, acid, reactive and direct azo dyes into aromatic amines and CotA-laccase oxidise these compounds into phenazines, phenoxazinones, and naphthoquinones. Secondly, whole-cells containing the overproduced enzymes were utilised in the two-step enzymatic conversion of the model mordant black 9 dye into sodium 2-amino-3-oxo-3H-phenoxazine-8-sulfonate, allowing to overcome the drawbacks associated with the use of expensive purified enzymes, co-factors or exquisite reaction conditions. Thirdly, cells were immobilized in sodium alginate, allowing to recycle the biocatalysts and to achieve very good to excellent final phenoxazine product yields (up to 80%) in water with less impurities in the final reaction mixtures. Finally, one-pot systems using recycled immobilized cells co-producing both enzymes resulted in the highest phenoxazinone yields (90%) through the sequential use of static and shaking conditions, controlling the oxygenation of reaction mixtures and the successive activity of azoreductase (anaerobic) and laccase (aerobic).